Moral Ekonomi Petani Kopi di Desa Bonto Tengnga Kecamatan Sinjai Borong Kabupaten Sinjai - Abdul Rahman . (Universitas Negeri Makassar, 2023)
ABSTRACTThis study aims to determine the economic morale of coffee farmers associated with local traditions and culture in Bonto Tengnga Village, Sinjai Borong District, Sinjai Regency. This type of research is qualitative research. Data collection is done through observation, interviews and documentation. The data analysis technique used is data reduction, data presentation and conclusion drawing as well as the data validation technique used is triangulation. The results of the study show that the socio-economic life of coffee farmers in Bonto Village is mutual assistance to meet economic needs both between the owner farmer and the working farmer as well as the farmer families who help in the coffee processing process. The tradition of coffee farmers in relation to their economy is that the local community has several beliefs, including determining an auspicious day before harvesting coffee in the hope that they will be given safety. After the harvest, the farmers held a thanksgiving event by calling relatives and neighbors to give thanks to Allah SWT for obtaining sufficient yields to make ends meet.